Qualidade de vida de pacientes com câncer de boca tratados com cirurgia primária : análise pré-operatória e pós-operatória - Viana, Thales Salles Angelim (2014)
Introduction: The increasing prevalence of chronic degenerative diseases, especially various types of malignant lesions, shows a major change in the morbidity and mortality of the world population profile. According to the World Health Organization (WHO), there were 14,1 million incident cases and 8,2 million cancer deaths in 2012. Oral cancer is a serious and growing problem in many parts of the world. Brazilian male population is considered the third highest risk for oral cancer in the world, after countries like France and India. The treatment of oral cancer is undoubtedly related to a decrease in quality of life (QOL), which can generate significant functional, aesthetic and emotional changes. The measurement of QOL allows monitoring, as well as understanding of the real impact of the disease and its treatment on patients lives. Objective: To measure the QOL of patients treated with primary surgery for oral cancer, through an analysis of preoperative and postoperative. Methods: A prospective cross-sectional study in which 54 patients treated with primary surgery for oral cancer from August 2012 to October 2013 were included. Patients were treated at the Hospital Haroldo Juaçaba - Cancer Institute of Ceará (HHJ-ICC) in Fortaleza, Ceará, Brazil. For analysis of QOL, the questionnaire of the University of Washington (UW-QOL) for head and neck cancer (CCP) at pre and post-operative was used. The clinicopathological profile and lifestyle were also collected. Categorical data were analyzed by means of confidence intervals and Fisher exact or Chi-square test. The variation in scores QOL the preoperative to the postoperative period was assessed using the Wilcoxon test (nonparametric data). Data were exported to the Statistical Packcage for Social Sciences and adopted a confidence of 95% (p<0,05) in all analyzes. Results: The prevalence was higher in males (72,2%; p=0,018) with a mean of 61,1±13,9 years old, with the majority having completed elementary school (33,3%; p=0,001) or incomplete (33,3%; p=0,001) and natural in the state (63%; p<0,001). As for lifestyle, most of the selected patients were smokers (81,5%), alcoholic (63,0%) and worked out in the sun (77,8%). The lesions were more prevalent in language, followed by lip and oral floor and classified primarily as stage IV (40,8%) and I (34,7%). QOL analysis, comparing the first phase and immediate postoperative, showed a drop in appearance scores, activity, recreation, swallowing, chewing, talking, shoulder function, saliva, and especially the palate (p=0,001). As for the areas of pain, mood and anxiety had improved. On the importance of pain domains, mood and anxiety stood out, with statistical significance compared with the postoperative phase. In the postoperative period, the domains speech and shoulder function were also statistically significant compared to the previous time. In absolute terms had pain, anxiety and swallowing were quite cited preoperatively and chewing and swallowing postoperatively. Most patients rated their QOL related to health and general as good and very good in the postoperative period. Conclusion: The UW-QOL was an effective tool in the analysis of the sample. Although still the most widely used treatment, surgical resection in the treatment of oral malignant lesions contributed negatively to QOL, especially on the functional aspects of the stomatognathic system. Even with the worsening of individual domains, patients classified as positive their overall QOL and health-related postoperative. Clinical Relevance: Identification of the most affected areas and its importance throughout surgical treatment for subsequent performance in policies for prevention and care to these patients. The reflection and the search for new technologies in cancer treatment are necessary.